PEMBERDAYAAN PENGRAJIN ANYAMAN DAUN PANDAN DI DESA MAMBEN LAUK KECAMATAN WANASABA KABUPATEN LOMBOK TIMUR - Abdullah, Wildan Rosad; Saputra, Aldi; Sudani, Ni Putu Eka Vannysia; Nurmelawati, Baiq; Mulya, Muhammad Rizki Adhe; Zarfani, Muhammad Ardian; Iskandar, Siska Rozana; Aryani, Maesa; Duljuhaini, Ria; Rahmayani, Desi; Fuadi, Helmy (Universitas Mataram, 2024)
The problems faced by pandan leaf craftsmen are one example of a problem in rural areas that needs to be addressed. Problems in rural areas can be overcome by carrying out development with community empowerment. Community empowerment by KKN PMD is carried out on craftsmen to increase the income and independence of craftsmen. This research aims to describe the stages of empowering pandan leaf craftsmen and the results of empowering pandan leaf craftsmen in Mamben Lauk Village, Wanasaba District, East Lombok Regency. The results of the research show that the empowerment of woven pandan leaves in Mamben Lauk Village has several stages, namely the survey stage, preparation for making products, making products packaging, promotion and marketing. Community empowerment activities through weaving pandan leaves in Mamben Lauk Village, Wanasaba District, East Lombok Regency, have provided several results, namely business development, increased awareness, increased independence, and increased community capacity and income distribution.